BUDDHIST SUPPORTS OF KING XETTHATHIRAT IN NONGKHAI - Panyavaro, Phramaha Prayad; Abhivaddhano, Phamaha Prateep; Phurithatto, Phra Wanchai; Munyapho, Jesada; Siridhammo, Phramaha Paitool (Journal of Buddhist Anthropology, 2021)
Xetthathirat is one of the greatest kings of the Lan Xang Kingdom. He is the king who rules both kingdoms at the same time that are the Lanna Kingdom and the Lan Xang Kingdom. Once he moved the capital from Luang Prabang to Vientiane as the new capital, he has supported Buddhism together with the development of the country. He also built the city wall, 120 temples within the city walls, restored of Phra That Luang and built many important Buddha images. In addition, His Majesty also preserved a large number of Buddhism in Nongkhai Province that's why King Xetthathirat's performances are concerned in temples, Buddha images and stone inscriptions. These are the evidence of His royal duties of supporting Buddhism in Nongkhai. The Buddhism supports in Nongkhai province of King Xetthathirat is divided into 3 aspects: 1) supported by building temples, 2) supported by building the Buddha images and 3) supported by the restoration of the stupas (Phra That Chedi). As a results from His Majesty supports of Buddhism in Nongkhai province make Buddhism there very prosperous up to now. Buddha temples and stupas have now become an important Buddhist tourist destination in Nongkhai Province. The stone inscriptions in the temples became important archaeological evidence regarding to the studies and researches of the history of Buddhism and royal duties about Buddhism supports in Nongkhai province of King Xetthathirat.